Double M-plasty in Patients with Basosquamous Carcinoma. A Case Report - Carlos Manuel Collado Hernández; Francisco Matos Figueredo; Vivian Pérez Núñez (Medisur)
Skin cancer is the most common malignant tumor in humans and its presence has increased in recent years. We report the case of an 86 years old patient who attended multidisciplinary tumors consultation at the Celia Sánchez University Hospital of Manzanillo because of a tumoral lesion on the forehead lasting for three years. The tumor presented a slow growth and caused occasional and spontaneous pain. The nodular lesion was located at a distance of 3 cm from the front left limit hairline. With the suspicion of a basal cell carcinoma, the sole technique of double m-plasty was used as treatment, which is unusual in this type of injury and in that location. The histological report indicated that it was the case of a basosquamous carcinoma. Post surgical evolution was satisfactory.